Combined effects of aging and low temperature, long time heating on pork toughness. (April 2019) - Li, Shengjie; Ma, Renchao; Pan, Jinfeng; Lin, Xinping; Dong, Xiuping; Yu, Chenxu
Abstract: The combined effects of aging and low temperature, long time heating (LTLT) on meat toughness were investigated. Pork loins were heated at 53 or 58 °C for up to 20 h, and shear force values, cooking loss, moisture content, collagen solubility, electrophoresis of myofibrillar proteins were determined. Structural changes in perimysium were also observed by light microscopy and scanning electron microscopy (SEM). Results showed that aging and LTLT cooking independently affected meat toughness, and higher temperature or longer time were required to decrease toughness of one-day aged meat to the same level as in 10-day aged meat. Collagen solubilization is suggested as the main reason for the tenderization effect of LTLT. Myofibrillar proteolysis might not occur during LTLT cooking, and will not be contributing to meat tenderness.